CIAT Financial Statements 2023 for the year ended 31 December: Including independent auditor's report - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2024)
CIAT’s financial mandate includes maintaining accountability and transparency in its finances, and to evaluate and communicate direct impact from our work to our donors, partners and the wider research and development community.